Integration of Pseudotargeted Metabolomics and Microbiomics Reveals That Hugan Tablets Ameliorate NASH with Liver Fibrosis in Mice by Modulating Bile Acid Metabolism via the Gut Microbiome - Wenran Dong; Ying Wang; Huajinzi Li; Huilin Ma; Yingxi Gong; Gan Luo; Xiaoyan Gao (Metabolites, 2025)
Background/Objectives: Non-alcoholic steatohepatitis (NASH) carries a high risk of developing hepatic fibrosis. Hugan tablets (HGTs), a traditional Chinese medicine, have exhibited potent anti-hepatic fibrosis effects, though the underlying mechanisms remain unclarified. This study aims to assess the efficacy of HGTs against NASH-related liver fibrosis in mice and investigate the underlying mechanisms via the integration of pseudotargeted metabolomics and microbiomics. Methods: C57BL/6 mice were fed a choline-deficient, ethionine-supplemented (CDE) diet and treated with HGTs. The therapeutic effects of HGTs in CDE mice were assessed. The underlying mechanism of HGTs was investigated by the integration of microbiomics, a pseudo-sterile model, untargeted followed by pseudotargeted metabolomics, and molecular docking. Results: HGTs alleviated NASH-related hepatic fibrosis in CDE mice and restored the composition of the gut microbiota. The depletion of the gut microbiota eliminated the anti-hepatic fibrosis effect of HGTs. HGTs increased intestinal 7-ketolithocholic acid and tauroursodeoxycholic acid via 7α/β-hydroxysteroid dehydrogenase (7α/βHSDH), while reducing deoxycholic acid (DCA) and taurodeoxycholic acid through inhibition of bile acid 7α-dehydratase (BaiE), leading to lower hepatic DCA. Six intestinal components of HGTs interacted with 7αHSDH, 7βHSDH, and BaiE, which are expressed in the bacterial genera altered by HGTs. Conclusions: HGTs alleviate NASH fibrosis by reshaping the gut microbiome, acting on microbial BA-metabolizing enzymes, and regulating the BA metabolism in the liver and gut.